Correlation Between Anemia And The Incidence Of Low Birth Weight (LBW) - Oktaviana Dewi Lolita; Ira Titisari; Sumy Dwi Antono (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Low Birth Weight (LBW) is newborn who weight less than 2,500 grams. LBW also has an impact on infant namely anemia, hypothermic, hyperbilirubinemia, hypoglyglyemi, respiratory syndrome. One major factor causes anemia during pregnancy. The update of this study is to discuss the relationship between anemia and LBW in developing countries, especially in the continents of Asia and Africa. The purpose of this study is to learn about anemia and LBW in developing countries on the Asian and African continents with literature review. The study design used is the study literature review by scoping study. A journal or article search involves using a keyword or keyword that